Pemanfaatan Museum Kereta Api Ambarawa sebagai Sumber Belajar dalam Meningkatkan Kreativitas Siswa - Marsheila Angella Kharisma Puteri; Syaiful Amin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study was to analyze the effectiveness of the Ambarawa Railway Museum as a learning resource in improving the creative thinking skills of eleventh-grade students at SMA Negeri 1 Ambarawa. This study employed a qualitative research method using observation and in-depth interviews with students involved in learning activities at the museum. The findings showed that the use of the museum provided a contextual and meaningful learning experience. Through direct interaction with the museum's collections and environment, students were able to develop creativity in observing, connecting, and interpreting historical evidence. In addition, students demonstrated the ability to generate ideas and reconstruct historical events based on the findings obtained during the learning process. The conclusion of this study indicates that the Ambarawa Railway Museum is an effective learning resource for enhancing students' creative thinking skills and strengthening their understanding of history. Therefore, the museum can be used as an alternative learning resource that supports more active and innovative history learning. Keywords: Ambarawa Railway Museum, Critical-Creative Thinking, Learning Resource